1991
DOI: 10.1136/bmj.303.6811.1179
|View full text |Cite
|
Sign up to set email alerts
|

Skin biopsy in general practice.

Abstract: and length of history (M Whitaker, personal communication). Some, albeit few, malignant lesions were not clinically recognised in this study and doctors should be wary of discarding skin specimens as malignant and incompletely excised lesions may recur. Referral for histological examination avoids delayed diagnosis and should effect prompt and adequate further treatment if required.In conclusion, the performance of skin biopsies by general practitioners could be improved. All skin specimens should be sent for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0
3

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 0 publications
2
2
0
3
Order By: Relevance
“…The broad geographical coverage and the high response rate suggest that the study practices were representative of practices throughout England that offer minor surgery; this is supported by the finding that the proportion of referred lesions that were malignant was closely similar to that found in other studies 6 7 8…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The broad geographical coverage and the high response rate suggest that the study practices were representative of practices throughout England that offer minor surgery; this is supported by the finding that the proportion of referred lesions that were malignant was closely similar to that found in other studies 6 7 8…”
Section: Discussionsupporting
confidence: 76%
“…Around 40% of lesions excised by general practitioners are not referred to a pathologist 3 4. Several researchers have reported diagnostic errors and incomplete excision of malignant lesions by general practitioners5 6 7 8 9 and have recommended mandatory pathological examination, a proposal supported by the Royal College of General Practitioners and other professional bodies 10…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies reported on the accuracy of the clinical diagnosis of dermatologists or nondermatologists, or both, using the histopathological diagnosis as the ''gold standard'' [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] with the number of cases ranging from 43 28 to 2935. 25 With 4451 analyzed skin specimens, the current study is to date the largest study of its kind.…”
Section: Discussionmentioning
confidence: 99%
“…La concordancia diagnóstica fue del 66%, cifra alta si comparamos con el 41-62% que se relaciona en la publicación de MCWilliam et al y aceptable comparada con la de Arribas et al [26][27][28][29] .…”
Section: Discussionunclassified